Evaluation of leaf extracts and essential oils against Fusarium oxysporum f.sp. pisi –the causal agent of pea wilt - VIVEK SINGH; PRADEEP KUMAR SINGH, MOHD. ALI*, MEHI LAL, ANIS KHAN (Indian Phytopathology, 2013)
Pulses are gaining importance globally, as they are the crop source of vegetable protein. The demand for protein is increasing by about 3.00 percent annually. Awareness, about the utility of pulses in human food, animal feed and soil health is in increasing day by day. However, with exploding world population, per capita availability of pulses is decreasing. With the increased irrigated area, pulses are further being pushed the marginal and sub-marginal lands because of their ability to survive under adverse conditions. They face tough competition with commercial crops, which have also greater stability in production. Pea is the second most important food legume in the world after pigeon pea. Wilt of pea caused by Fusarium oxysporum f.sp.pisi (Linford) Snyder and Hansen is one of the most important disease of pea.